UNVEILING THE DILEMMA: DO FINANCIAL DERIVATIVES IMPERIL OR PROPEL ECONOMIC PROSPERITY? - MILOȘ Laura Raisa; MILOȘ Marius Cristian (Management of Sustainable Development)
The study delves into how regulated derivatives trading influences economic growth across 21 countries, spanning from 1995 to 2022, encompassing major economies like the USA, UK, India, Brazil, Canada, and Australia. While derivatives markets are often linked with the 2008 financial crisis, our research explores their potential to positively impact the economy through various pathways detailed in the paper. Employing a dynamic panel data model (GMM) mitigates potential endogeneity concerns. Our findings reveal notable insights: we identify a positive association between the expansion of regulated derivatives trading and economic growth, evident in both percentage change and per capita GDP. Additionally, inflation shows a negative correlation with economic growth, while trade openness and fertility rates exhibit positive correlations. Notably, our study uncovers unexpected outcomes, diverging from existing literature, particularly concerning the relationships involving foreign direct investments, gross domestic savings, government consumption expenditure, and economic growth.